-3+5×(-2)=
6×(-5)+3×(-4)=
(-2)la puterea a 8 a :(-2)la puterea a 5 a-(-7)×(-2)=
-4+8:(-2)-(1998)la puterea 0=
Răspunsuri la întrebare
Răspuns de
0
-3 + 5×(-2) = - 3 - 10 = - 13
6×(-5)+3×(-4) = - 30 - 12 = - 42
(-2)^8 : (-2)^5 - (-7)×(-2) =
= (-2)^3 - 14 =
= - 8 - 14 =
= - 22
-4 + 8:(-2) - 1998^0 =
= - 4 - 16 - 1 =
= - (4+16+1) =
= - 21
6×(-5)+3×(-4) = - 30 - 12 = - 42
(-2)^8 : (-2)^5 - (-7)×(-2) =
= (-2)^3 - 14 =
= - 8 - 14 =
= - 22
-4 + 8:(-2) - 1998^0 =
= - 4 - 16 - 1 =
= - (4+16+1) =
= - 21
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Informatică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă